Extended surgery of antero-superior mediastinum - Aprile, Vittorio; Korasidis, Stylianos; Bacchin, Diana; Ambrogi, Marcello Carlo; Lucchi, Marco (Current Challenges in Thoracic Surgery; Vol 1 (December 2019): Current Challenges in Thoracic Surgery, 2019)
Surgery of large mediastinal tumors is a great challenge for the surgeons due to wide number of organs that may be involved despite the narrow space. Any treatment plan should be thoroughly planned step-by-step since the diagnosis to assess the features of the tumor and its relationship with the surrounding organs. Radicality is main goal of the surgeons even if this includes the sacrifice of some structure and the reconstruction of others. Cooperation with the anesthesiologist and surgeons of other speciality is often necessary especially in case of infiltrating tumors. Evolution of the surgical technique end of the peri-operative management as well as the availability of new-generation prosthesis and the increasingly widespread of extracorporeal circulation (ECC) have turned this kind of surgery into a feasible, safe and effective procedure. The cornerstones of this surgery are a detailed preoperative assessment, the ability to prevent any potential complication and involve a multidisciplinary equipe.